Reshaping Urbanization in Rwanda : Urbanization and the Evolution of Rwanda’s Urban Landscape - World Bank Group (World Bank, Washington, DC, 2017)
The objective of this report is to inform the government’s policies and strategies on urbanization as a driver of economic development, job creation, and poverty reduction. Note 1 examines Rwanda’s urbanization process since 2002 by analyzing satellite images and other sources. This note presents and analyses the core features and trends of Rwanda’s urbanization process. In the first part, it lays out the overall trends in Rwanda’s levels of urbanization and the primary trends in urban expansion of Rwanda’s key cities, and presents central legal and institutional elements that influence and inform the dynamics of urbanization. Second, it analyses the characteristics and spatial economy of the urban system. Third, it provides an analysis of key characteristics of connectivity of the urban system, domestically and with perspectives to regional connectivity. Last, the note lays out a set of policy implications.